Jugular thrombophlebitis in horses: A review of fibrinolysis, thrombus formation, and clinical management - Dias, Deborah Penteado Martins [UNESP]; De Lacerda Neto, José Corrêa [UNESP] (My University, 2013)
Thrombophlebitis of the jugular vein is commonly observed in horses, particularly during intensive care, and leads to local and systemic inflammatory responses as well as head and neck circulatory impairment. Thrombolytic therapy is widely used in human practice with the aim of thrombus dissolution and recanalization of the injured vessels. There are similarities between human and horse coagulation and fibrinolytic processes. This review examines the fibrinolytic system, thrombus formation, and the clinical management of jugular thrombophlebitis, including thrombolytic therapy. There is evidence that early regional thrombolytic therapy for jugular thrombophlebitis in horses may be effective to achieve sustained recanalization.